Acute Increase in O-GlcNAc Improves Survival in Mice With LPS-Induced Systemic Inflammatory Response Syndrome - Silva, Josiane Fernandes; Olivon, Vania C.; Mestriner, Fabiola Leslie A. C.; Zanotto, Camila Ziliotto; Ferreira, Raphael Gomes; Ferreira, Nathanne Santos; Silva, Carlos Alberto Aguiar; Luiz, João Paulo Mesquita; Alves, Juliano Vilela; Fazan, Rubens; Cunha, Fernando Queiróz; Alves-Filho, Jose Carlos; et al. (Frontiers in Physiology, 2020)
Sepsis is a systemic inflammatory response syndrome (SIRS) resulting from a severe infection that is characterized by immune dysregulation, cardiovascular derangements, and end-organ dysfunction. The modification of proteins by O-linked N-acetylglucosamine (O-GlcNAcylation) influences many of the key processes that are altered during sepsis, including the production of inflammatory mediators and vascular contractility. Here, we investigated whether O-GlcNAc affects the inflammatory response and cardiovascular dysfunction associated with sepsis. Mice received an intraperitoneal injection of lipopolysaccharide (LPS, 20 mg/Kg) to induce endotoxic shock and systemic inflammation, resembling sepsis-induced SIRS. The effects of an acute increase in O-GlcNAcylation, by treatment of mice with glucosamine (GlcN, 300 mg/Kg, i.v.) or thiamet-G (ThG, 150 μg/Kg, i.v.), on LPS-associated mortality, production and release of cytokines by macrophages and vascular cells, vascular responsiveness to constrictors and blood pressure were then determined. Mice under LPS-induced SIRS exhibited a systemic and local inflammatory response with increased levels of interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor (TNF-α), as well as severe hypotension and vascular hyporesponsiveness, characterized by reduced vasoconstriction to phenylephrine. In addition, LPS increased neutrophil infiltration in lungs and produced significant lethality. Treatment with GlcN and ThG reduced systemic inflammation and attenuated hypotension and the vascular refractoriness to phenylephrine, improving survival. GlcN and ThG also decreased LPS-induced production of inflammatory cytokines by bone marrow-derived macrophages and nuclear transcription factor-kappa B (NF-κB) activation in RAW 264.7 NF-κB promoter macrophages. Treatment of mice with ThG increased O-glycosylation of NF-κB p65 subunit in mesenteric arteries, which was associated with reduced Ser536 phosphorylation of NF-κB p65. Finally, GlcN also increased survival rates in mice submitted to cecal ligation and puncture (CLP), a sepsis model. In conclusion, increased O-GlcNAc reduces systemic inflammation and cardiovascular disfunction in experimental sepsis models, pointing this pathway as a potential target for therapeutic intervention.